Restructuring of the Country’s Economy: A Bibliometric Analysis of the Available Research - Khaustova Viktoriia Ye.; Trushkina Nataliia V.; Pronoza Pavlo V.; Yudenko Yevhen V. (Problemi Ekonomiki)
At the current stage of global economic transformations, the issues of restructuring the economies of countries around the world are extremely important. These issues are particularly relevant in the context of a changing, unstable external environment and crisis situations worldwide. For Ukraine, economic restructuring should become one of the strategic tasks of post-wartime reconstruction and State development, ensuring the resilience of the economic system. Experts assert that Ukraine’s economic system continues its transformation under conditions of global instability, geopolitical challenges, and internal structural changes. Notably, the most significant structural changes have been observed in recent years in sectors such as agriculture (the transition from a raw material model to the production of finished goods with high added value); the IT industry (a strategic direction for service exports); and energy (the shift towards decarbonization and green energy); defense-industrial complex (strengthening of innovative potential); transport and logistics complex (development of modern transport and logistics infrastructure), etc. It should be noted that new challenges, risks, external threats, and crisis phenomena affecting the structural transformations of the national economy require the search for and substantiation of the theoretical and methodological approaches to determining the priority areas for restructuring the economy and developing relevant instruments and applied recommendations for their implementation in practice. Therefore, this study is dedicated to analyzing the relationship between restructuring and the country’s economy using a bibliometric approach. The aim of the article is to identify trends and key research directions on the restructuring of the country’s economy based on bibliometric analysis using VOSviewer software. It is found that the restructuring of the country’s economy is primarily viewed from the perspectives of systemic, innovative, circular, and strategic approaches. This, in turn, requires the formation of a fundamentally new economic model based on strategic, innovative, green, digital, and security principles. The results of the research will provide a comprehensive understanding of the current state and future prospects of research on the restructuring of the country’s economy. This, in turn, may assist in identifying priority measures to stabilize the socioeconomic situation during martial law, as well as in formulating a more effective strategy for the recovery of Ukraine’s economy in the post-wartime period.